Underload work and Challenging Work: Overcoming Boredom among Millennials - Rihhandini, Don Ozzy; Parahyanti, Endang (Bina Nusantara University, 2023)
The research aimed to explore the moderation role of challenge in the relationship between underload work and boredom at work, especially among millennial employees. As part of the current productive age and some had even occupied essential positions in the company, millennials had characteristics that were easier to get bored than other generations, which could increase millennials’ vulnerability to feeling bored at work. Therefore, a special strategy was needed to deal with boredom among millennials to maintain company productivity and psychophysical health in millennials. The research involved 327 millennials employee in Indonesia aged 23-40. Data were collected from December 2021 – January 2022 via a Google Form. The data were analyzed using simple moderation by PROCESS Hayes. The findings show that boredom can be predicted by three underload work variables: perception of underload work, the expectation of workload, and desire for the workload. The moderation role of challenge can only be found to reduce the effect of underload work perception on boredom but not on workload expectation or workload desire. Based on this result, it can be concluded that seeking challenges or adding responsibilities at work can prevent boredom among employees who perceive low workloads in their current state. As a result, organizations must provide employees with the opportunity and support to take on new challenges at work. Employees must also be proactive in seeking new challenges to avoid boredom.